ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERPINDAHAN MEREK PADA PRODUK SMARTPHONE - Khasanah, Aulia Uswatun; Kuswati, Rini (Benefit: Jurnal Manajemen dan Bisnis, 2013)
This study aimed to determine the effect of product quality, advertising, and variety seeking on brand switching. The samples in this study were students of Muhammadiyah University of Surakarta, amounting to 100 respondents . Sampling technique in this study was the purposive sampling and convenience sampling. Data analysis method used is normality test and test multiple linear regression analysis with t test, F test, and the coefficient of determination (R). In this study meets the data for normal distribution. Hypothesis test showed that the quality of products and variety seeking has significant influence with t respectively 6.869 and 3.846, while no ads variables have a significant effect evidenced by the t value of -0.970. In the F test showed that together thevariable quality of the product, advertising, and variety seeking significant effect on brand switching. The coefficient of determination (R2) of 59.9 %This study aimed to determine the effect of product quality, advertising, and varietyseeking on brand switching. The samples in this study were students of Muhammadiyah Universityof Surakarta, amounting to 100 respondents . Sampling technique in this study was the purposivesampling and convenience sampling. Data analysis method used is normality test and test multiplelinear regression analysis with t test, F test, and the coefficient of determination (R). In this studymeets the data for normal distribution. Hypothesis test showed that the quality of products andvariety seeking has significant influence with t respectively 6.869 and 3.846, while no ads variableshave a significant effect evidenced by the t value of -0.970. In the F test showed that together thevariable quality of the product, advertising, and variety seeking significant effect on brandswitching. The coefficient of determination (R2) of 59.9 %